2019
DOI: 10.1053/j.ajkd.2019.01.028
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Angiogenesis Markers With Acute Kidney Injury and Mortality After Cardiac Surgery

Abstract: Each author contributed important intellectual content during manuscript drafting or revision and accepts accountability for the overall work by ensuring that questions pertaining to the accuracy or integrity of any portion of the work are appropriately investigated and resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 51 publications
(52 reference statements)
2
44
0
Order By: Relevance
“…The results presented by Mansour et al 7 corroborate the concept that enhanced formation of neovascularization can help preserve peritubular capillaries, mitigate tubulointerstitial fibrosis, and stabilize kidney function after injury. 11,12 However, unknown factors may influence the relationship between angiogenic markers and AKI or mortality.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…The results presented by Mansour et al 7 corroborate the concept that enhanced formation of neovascularization can help preserve peritubular capillaries, mitigate tubulointerstitial fibrosis, and stabilize kidney function after injury. 11,12 However, unknown factors may influence the relationship between angiogenic markers and AKI or mortality.…”
mentioning
confidence: 53%
“…In this issue of AJKD, 3 markers of angiogenesis are reported from the TRIBE-AKI cohort, a large multicenter prospective study performed between 2007 and 2010 in 1,444 patients at high risk for AKI undergoing cardiac surgery. 7 Of the cohort, 492 (34%) developed AKI (88% had stage 1) and only 8% had prolonged AKI (≥7 days). After 1 year, 6% of participants had died.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The Translational Research Investigating Biomarker Endpoints for Acute Kidney Injury (TRIBE-AKI) cohort study on adults undergoing cardiac surgery found that proangiogenic markers, such as VEGF, correlated with a reduced risk of AKI and mortality, but antiangiogenic VEGFR-1 was associated with an increased risk of AKI and mortality. 148 Moreover, VEGF-C and VEGF-D, which are the main ligands for lymphangiogenesis, are abundantly expressed in tubules and increased in the serum and urine after injury. They are involved in renal inflammation and possibly serve as novel urinary biomarkers for AKI and the progression of kidney disease.…”
Section: Growth Factors May Serve As Biomarkersmentioning
confidence: 99%
“…149 In addition, increased urine or plasma FGF-23 levels may be promising novel biomarkers for AKI and other adverse outcomes in critically ill patients. 148,[150][151][152] A previous study also showed that low IGF-1 levels might serve as mortality predictors in AKI patients in the ICU. 89…”
Section: Growth Factors May Serve As Biomarkersmentioning
confidence: 99%